Teaching and learning to read words: contributions of behavior analysis. (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
The aim of this study was to investigate the applicability of a program for teaching the reading of words based on principles of behavior analysis and the training of kindergarten teachers to implement it in the classroom. A total of three teachers and their respective classes participated. The procedure consisted of: 1) Reading pre-test with the pupils and recording the behavior of the teachers, 2) Meetings with teachers to present and discuss the teaching program, 3) Implementation of the program of instruction by the teachers, 4) Post-test with the pupils and evaluation of the teaching program by the teachers. The program included teaching and/or tests that included: dictated word-word building, printed word-word building, dictated word-printed word, dictated word-picture, picture-printed word, printed word-picture, picture-word building, and printed word naming. In the pre-test, most pupils could not name most of the words. In the post-test, pupils in Classes A, B and C, named, respectively, 77.91%, 90.71% and 96.26% of the words taught, and 50%, 83.57% and 70% of the generalization words. It may be concluded that the educational program was appropriate for teaching reading comprehension in a collective situation and that the teachers were duly trained to use it.
Keywords: Educational technology; Equivalence relations; Teaching how to read; Teacher training